Migração intrametropolitana e movimentos pendulares na região metropolitana de Belo Horizonte: o caso do município de Contagem - 1991/2000 - Marcy Regina Martins Soares (2006)
The main purpose of this work is to analyse the displacement of the population of Belo Horizonte to Contagem, which occurred during the past decade, with a view toward exploring the migratory, intrametropolitan and oscillatory movements motivated exclusively by work. Oscillatory movements are understood to be the frequent dislocations between the places of residence and of work. The Demographis Census of 1991 and that of the year 2000, as well as the Survey of Origin and Destination (OD) carried out in 2001 by the Fundação João Pinheiro, were used as sources for the data.In order to attain the intended purpose, two anlyses were carried out; the first of these dealing with intrametropolitan migration, i.e., with persons emigrating from Belo Horizonte to the remaining municipalities of its metropolitan area (RRMBH), putting the municipality of Contagem in relief. The second analysis deals with the oscillations between the municipalities of Belo Horizonte and Contagem, which are motivated exclusively by opportunities for work.A process of demographic inversion is occurring in the Brazilian metropolitan areas since the seventies, that is, the population in the capitals is decentralizing as a result of other municipalities in said metropolitan regions. Belo Horizonte´s expansion has been due to real estate speculation and the job market. The real estate speculation caused such high prices in landed property that a home in the capital became unfeasible and inaccessible for low-income individuals. People started to live more and more distant from the nucleus, but returned to it daily in order to work. This has occurred, and is occurring, because the job market at the place of destination cannot absorb the labour that is becoming available.